2021
DOI: 10.1021/acs.jpca.1c08132
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrafast Quantum Dynamics of Photoexcited Adenine–Thymine Basepair Investigated with a Fragment-based Diabatization and a Linear Vibronic Coupling Model

Abstract: In this contribution we present a quantum dynamical study of the photoexcited hydrogen bonded base pair adenine−thymine (AT) in a Watson−Crick arrangement. To that end, we parametrize Linear Vibronic Coupling (LVC) models with Time-Dependent Density Functional Theory (TD-DFT) calculations, exploiting a fragment diabatization scheme (FrD) we have developed to define diabatic states on the basis of individual chromophores in a multichromophoric system. Wavepacket propagations were run with the multilayer extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…40 Such a process is much less efficient in AT base pairs where most of the population follows intramolecular decays to dark nπ* states. 41 Similar approaches applied to AA stacked dimers predicts a population of the CT state in 50 fs, 42 and for GC tetramers it indicates that the population of intrastrand CT is favored over the interstrand one (unpublished results). Whereas, at the state of the art, QD studies are confined to the ultrafast regime, when the system has not had time to undergo large distortions, semiclassical surface hopping approaches can investigate longer time scales.…”
Section: Does Not Mean Stiff; Turtles and Hares Play Togethermentioning
confidence: 84%
See 1 more Smart Citation
“…40 Such a process is much less efficient in AT base pairs where most of the population follows intramolecular decays to dark nπ* states. 41 Similar approaches applied to AA stacked dimers predicts a population of the CT state in 50 fs, 42 and for GC tetramers it indicates that the population of intrastrand CT is favored over the interstrand one (unpublished results). Whereas, at the state of the art, QD studies are confined to the ultrafast regime, when the system has not had time to undergo large distortions, semiclassical surface hopping approaches can investigate longer time scales.…”
Section: Does Not Mean Stiff; Turtles and Hares Play Togethermentioning
confidence: 84%
“…QD studies of the early photodynamics of GC and AT base pairs in the gas phase based on linear vibronic coupling (LVC) models parametrized with TD-DFT show that within 100 fs most of the initial photoexcited population on Gua and a substantial part of the one on Cyt decay to a G­( + )-C­( − ) CT state, which should afterward lead to PCET . Such a process is much less efficient in AT base pairs where most of the population follows intramolecular decays to dark nπ* states . Similar approaches applied to AA stacked dimers predicts a population of the CT state in 50 fs, and for GC tetramers it indicates that the population of intrastrand CT is favored over the interstrand one (unpublished results).…”
Section: The Polymer (Oligonucleotides): Large Does Not Mean Stiff; T...mentioning
confidence: 99%
“…FrD-LVC has instead recently been used to study the competition between intrachromophore internal conversions (e.g., ππ* → nπ*) and interchromophore excitonic and charge transfer (CT) dynamics in the Watson−Crick GC and AT base pairs. 31,32 The possible occurrence of CT and Proton Coupled Electron transfer (PCET) processes in oligonucleotides has been the focus of very intense research activity in the last years, as shown, just to cite some of the contributions, by refs 39−50. Moreover, oligonucleotides have been an important playground for many methodological studies dealing with the analysis of CT states and discussing the accuracy of different electronic methods in their treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the QD simulations, we exploit the recently developed fragment diabatization parametrization of a linear vibronic coupling (FrD‐LVC) model [36] from time‐dependent density functional theory (TD‐DFT) calculations. On the time‐scale of interest of this study, the system is rigid enough to be amenable to a description in terms of low‐order Taylor‐expansion model Hamiltonians, for which nonadiabatic QD simulations are particularly effective, as shown by our recent study of GC and AT photoactivated dynamics in the gas phase [36,37] . We also exploit advances in the multiconfiguration time‐dependent Hartree (MCTDH) method [38,39] to carry out these high dimensional QD simulations, namely its extension to multilayer (ML) formalism, [40,41] and its implementation within the Quantics package [42,43]…”
Section: Introductionmentioning
confidence: 99%